IRRI’s Farm Household Survey Database - De Leon, Dehner M.; Pede, Valerien (International Rice Research Institute, 2024)
The FARM HOUSEHOLD SURVEY DATABASE is a collection of farm level datasets on rice productivity, fertilizer and pesticide use, labor inputs, prices, income, demographics, farm characteristics, and other related data on rice production in farmer's fields. It is a rich collection of actual farm and household level data collected through personal farmer interviews, farm record keeping, and periodic monitoring of farm activities from various sites in different rice growing countries of Asia. The data collection was done by the International Rice Research Institute's Sustainable Impact through Rice-based Systems Department (formerly Agri-food Policy Platform and Social Sciences Division) in collaboration with NARES partners in various parts of the globe. These datasets are part of the output of the various research projects undertaken by the SIRS staff and hence made available to interested users.   Some valuable panel dataset are from the Central Luzon Loop survey that dates back to the mid 1960's up to present.